2023
DOI: 10.21053/ceo.2022.01235
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of mRNA and lncRNA Expression Profiles in Age-Related Hearing Loss

Abstract: Objectives. Age-related hearing loss (ARHL), or presbycusis, is caused by disorders of sensory hair cells and auditory neurons. Many studies have suggested that the accumulation of mitochondrial DNA damage, the production of reactive oxygen species, noise, inflammation, and decreased antioxidant function are associated with subsequent cochlear senescence in response to aging stress. Long non-coding RNA (lncRNA) has been reported to play important roles in various diseases. However, the function of lncRNA in AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…With the analysis of the co-expression profiles of mRNAs and lncRNAs in the ARHL-associated RNA sequencing dataset, Kim et al (2023) identified 112 mRNAs and 10 lncRNAs with relatively high expression in the cochlea of aged mice. Wang et al (2017) also demonstrated that in the Chinese population, the polymorphisms in LncRNA HOTAIR also could affect the risk of NIHL.…”
Section: Lncrna In Hearing Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…With the analysis of the co-expression profiles of mRNAs and lncRNAs in the ARHL-associated RNA sequencing dataset, Kim et al (2023) identified 112 mRNAs and 10 lncRNAs with relatively high expression in the cochlea of aged mice. Wang et al (2017) also demonstrated that in the Chinese population, the polymorphisms in LncRNA HOTAIR also could affect the risk of NIHL.…”
Section: Lncrna In Hearing Lossmentioning
confidence: 99%
“…LncRNAs are associated with a variety of diseases, including tumors, cardiovascular diseases, and inflammatory diseases. The role and mechanism of lncRNAs in hearing loss have been relatively poorly reported, compared to studies of miRNAs With the analysis of the co-expression profiles of mRNAs and lncRNAs in the ARHL-associated RNA sequencing dataset, Kim et al (2023) identified 112 mRNAs and 10 lncRNAs with relatively high expression in the cochlea of aged mice. Wang et al (2017) also demonstrated that in the Chinese population, the polymorphisms in LncRNA HOTAIR also could affect the risk of NIHL.…”
Section: Lncrna In Hearing Lossmentioning
confidence: 99%